Analisis Perbandingan Tegangan Tembus Antara Minyak Terpurifikasi dan Non Terpurifikasi Pada Transformator Unit 1 PLTA MALEA 2x45 MW - Reza Alfirdaus, Muh; Saini, Makmur; Sonong (Politeknik Negeri Ujung Pandang, 2026)
This study aims to analyze the comparison of breakdown voltage between purified and non-purified transformer oil in the Unit 1 transformer at PLTA Malea. The research focuses on evaluating the quality of transformer oil as an insulating and cooling medium to maintain transformer performance and reliability. The research method used was an experimental method by conducting breakdown voltage (BDV) tests on transformer oil samples before and after the purification process. The testing was carried out using an Insulating Oil Tester in accordance with the IEC 60422-2013 standard, with an electrode gap of 2.5 mm, and each sample was tested six times to obtain the average breakdown voltage value. In addition, supporting tests including viscosity and moisture content measurements were conducted to evaluate the changes in the physical characteristics of the transformer oil. The results showed that the non-purified transformer oil had an average breakdown voltage of 55.11 kV, which was considered unsuitable for operation because it was below the minimum standard. After the purification process, the average breakdown voltage increased significantly to 77.95 kV and met the operational requirements based on the IEC 60422-2013 international standard. These results indicate that transformer oil purification is effective in improving dielectric strength and insulation quality, and therefore can be recommended as a preventive and corrective maintenance method to maintain transformer reliability and extend its operational lifespan.